Implementation of Local Batak Simalungun Culture in Character Building of Students at SMP Negeri 1 Raya Kahean - Siregar, Hotma (Lembaga Riset Mutiara Akbar NOMOR AHU-0003295.AH.01.07 TAHUN 2021, 2025)
This study aims to examine the implementation of local Batak Simalungun culture at SMP Negeri 1 Raya Kahean, Simalungun Regency, through the Simalungun Language and Script subject in building student character. This study uses a qualitative descriptive approach with data collection techniques in the form of observation, interviews, and documentation. Data analysis is carried out through the stages of data reduction, data presentation, and verification. The results of the study indicate that the learning of Simalungun Language and Script in grade IX has been implemented systematically and has made a real contribution to the preservation of Batak Simalungun cultural values. Teachers consistently integrate positive cultural values ??through contextual teaching materials and learning strategies. The novelty of this study lies in the finding that the Simalungun Language and Script subject has a dual function, not only as a vehicle for preserving local culture, but also as a medium for building student character that is structured and integrated into formal learning. Different from previous studies that tend to place local content only as cultural content, this study demonstrates its role as a strategic pedagogical instrument in local wisdom-based character education at the junior high school level.